Suitability of Fatha Limestone rocks in Sharqat Area for Riprap - Mohammed Rashed Abood; Muhand Essa Kheder (Tikrit Journal of Pure Science, 2023)
The study aims to evaluate suitability of Fatha limestone rocks in Sharqat Area for Riprap. The exposed rocks belongs to Fatha &Injana Formations in addition to quaternary deposits, Three stations were chosen to studied the limestone rocks in the north west plunge of Makhul anticline, Petro physical tests show the values(6.4-9.1)% (2.15-2.21)gm/cm3 (2.58-2.64) for Absorption, Dry density and Specific gravity respectively while the mechanical and chemical tests show the values(12-20) Mpa, (38-43)%, (5-12.5)% for unconfined compression strength, mechanical abrasion and chemical abrasion respectively, these properties of limestone rocks are suitable for Riprap purposes according to [1], and according to [2], are not  suitable because the absorption values out  of the specification. And not suitable according to [3], because the values of absorption out of the specifications.